Digital Marketing Transformation by Implementing SEO Concepts in MSMEs. Case Study: CV Asa Nusantara Resources Malang - Diovianto Putra Rakhmadani; Maliana Puspa Arum (Universitas muhammadiyah malang, 2022)
Marketing is an activity that spearheads a business, without a proper marketing strategy, a business will find it difficult to get good sales. In the industrial era 4.0, competition between businesses is getting tighter, this underlies the need for a digital marketing transformation to increase the level of competition with other business players. Digital Marketing is an effort to promote a brand using digital media that can reach consumers in a timely, personal, and relevant manner. This type of digital marketing includes many of the techniques and practices contained in the internet marketing category. MSME players certainly want to develop their business following industry 4.0 trends, especially in the marketing sector. The marketing digitalization movement replaced the activities they had been doing such as marketing through billboards, banners, and word of mouth promotion. This will begin to erode along with the widespread use of technology as a marketing medium. In addition, with the high level of competition, it is necessary to carry out digital marketing transformation efforts for MSMEs to increase competitiveness, brand awareness and marketing strategies. This study uses a website development method with SEO (Search Engine Optimization) techniques and produces a store website that can be used to display MSME business profiles and shop searches that are indexed on google search with SEO techniques so as to produce a digital marketing model that works better than conventional marketing.